(untitled) (Swiss Medical Weekly, 2016)
QUESTIONS UNDER STUDY: High blood pressure, the single leading health risk factor worldwide, contributes greatly to morbidity and mortality. This study aimed to add to the understanding of diagnosed and undiagnosed high blood pressure in Switzerland and to evaluate adherence to hypertension guidelines. METHODS: Included were 3962 participants from the first (2001–2003) and second (2010–2011) follow-ups of the population-based Swiss Cohort Study on Air Pollution and Lung and Heart Disease in Adults. High blood pressure was defined as blood pressure ≥140/90 mm Hg and the prevalence of doctor-diagnosed hypertension was based on questionnaire information. RESULTS: High blood pressure was found in 34.9% of subjects, 49.1% of whom were unaware of this condition; 30.0% had doctor-diagnosed hypertension and, although 82.1% of these received drug treatments, in only 40.8% was blood pressure controlled (<140/90 mm Hg). Substantial first-line beta-blocker use and nonadherence to comorbidity-specific prescription guidelines were observed and remained mostly unexplained. Age-adjusted rates of unawareness and uncontrolled hypertension were more than 20% higher than in the USA. CONCLUSIONS: There is room for improvement in managing hypertension in Switzerland. Population-based observational studies are essential for identifying and evaluating unmet needs in healthcare; however, to pinpoint the underlying causes it is imperative to facilitate linkage of cohort data to medical records.